TRANSLATION OF BALINESE MATERIAL CULTURAL TERMS FROM INDONESIAN INTO ENGLISH - Astina, Made Arya (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
This study is concerned with the translation of material cultural terms found in the bilingual book entitled The Bali Arts Festival Album and their translation into English. There are two things being discussed in this study. The first problem is how the semantics frame elements of Balinese cultural terms in The Bali Art Festival Album are compared with their translation equivalents? The second one is what translation procedures are adopted to translate the cultural terms in The Bali Art Festival Album? The cultural terms found in the book entitled The Bali Arts Festival Album were analyzed by using frame semantic analysis (Fillmore, 1982) and elaborated into componential analysis (Newmark, 1988). The translation procedures implemented in the translation of those cultural terms were analyzed based on the procedures proposed by Vinay and Darbelnet (in Venuti, 2000). The material cultural terms in the book entitled The Bali Arts Festival Album are identified. They are Balinese cultural terms. The translator applied two procedures of translation in translating the Balinese cultural terms. They are borrowing and literal.
Keywords: Cultural terms, semantic frame elements, componential analysis, and translation procedures